Towards BPM@Runtime - Loja, Luiz Fernando Batista; Paiva, Sofia L. Costa; Oliveira, Juliano Lopes (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2020: Anais do II Workshop em Modelagem e Simulação de Sistemas Intensivos em SoftwareDO - 10.5753/mssis.2020.12491, 2020)
Producing software to manage Business Processes (BP) in Information Systems (IS) requires considerable effort and time. This paper describes a software component that uses a Model-Driven Engineering (MDE) approach to support BP management in IS into the context of an IS application framework. The BP Manager component allows the deﬁnition of BP models using a high-level language, that is integrated with others framework components to generate the IS applications. This component has important improvements compared to other BP management tools, such as support for collaborative modeling and support for the execution of empirical and ad hoc processes. Furthermore, the integration of the BP management component into the framework brings signiﬁcant increases in productivity of IS software development and maintenance.